2022
DOI: 10.1021/jacs.2c00647
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of the Broad-Spectrum Antibiotic Amycolamicin

Abstract: The total synthesis of the antibiotic amycolamicin with a hybrid molecular architecture composed of five ring systems, which exhibits potent antibacterial activity against a wide range of drug-resistant bacteria, has been achieved in a convergent manner. A protecting-group-free intramolecular Diels–Alder reaction of a hydroxy tetraenal intermediate promoted by two equivalents of Et2AlCl, which proceeds highly diastereoselectively via an endo-equatorial transition state, has been utilized to construct the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 28 publications
0
10
1
Order By: Relevance
“…In light of these findings, a chiral directing group appeared necessary to achieve high levels of stereoselectivity in the critical IMDA on the way to 2 . Contrary to Kuwahara's [12] and also Baran's [13] findings, we had not expected a dramatic change in the stereochemical outcome of the IMDA for substrates incorporating a free allylic hydroxy group, such as in dodecatetraenals 9 a or 9 b .…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…In light of these findings, a chiral directing group appeared necessary to achieve high levels of stereoselectivity in the critical IMDA on the way to 2 . Contrary to Kuwahara's [12] and also Baran's [13] findings, we had not expected a dramatic change in the stereochemical outcome of the IMDA for substrates incorporating a free allylic hydroxy group, such as in dodecatetraenals 9 a or 9 b .…”
Section: Discussioncontrasting
confidence: 89%
“…Our route towards acid 2 is robust and scalable and at this point has allowed us to prepare multiple 100 mg quantities of ester 38 (only part of which has been converted into acid 2 ). However, we do recognize that compared to Kuwahara's synthesis [12] of the related decalin 8 a , which formally can be converted into 11 in two steps, our route requires more steps, as no chiral auxiliary and associated manipulations are required in Kuwahara's case. It is important to note, however, that earlier studies by Marshall had revealed the formation of 1 : 1 mixtures of the (desired) endo ‐equatorial and endo ‐axial products in the IMDA of 7‐alkoxy‐2,8,10‐undecatrienals [22b] .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In stark contrast, when the TBS group was removed to deliver free allylic alcohol 22 , the same intramolecular DA reaction provided the desired product ( 23 ) as a single diastereomer in 51 % isolated yield (as confirmed through X‐ray crystallography [12] ). The chelation between the free hydroxyl group and Lewis acid is essential for the selectivity [5b] …”
Section: Figurementioning
confidence: 99%